TINGKAT KEPUASAN IBU BERSALIN BERDASARKAN UMUR, PARITAS, PENDIDIKAN TERHADAP PELAYANAN KEBIDANAN - Januar Dwi Christy (Akademi Kebidanan Griya Husada Surabaya, 2018)
In simple terms, satisfaction is an attitude based on perceived quality of the patient. Patient satisfaction depends on the appearance of services offered in relation to his expectations. Quality midwifery services are midwifery services that can satisfy every user of midwifery services according to the level of satisfaction of the average population, and implementation in accordance with the code of ethics and professional service standards applied. Based on a preliminary study at Anugerah Surabaya RB on April 5, 2018, 4 people were less satisfied with midwifery services provided. The purpose of the study was to determine the level of satisfaction of maternity services for midwifery services. Method: This study used a descriptive method with accidental sampling technique in which sampling was carried out on individuals who were easily found with a population of 72 mothers giving birth using a questionnaire as a research instrument. Results: Based on the results of research from 72 mothers who visited Anugerah Surabaya RB, 9.7% felt very satisfied with midwifery services, 87.5% were satisfied with midwifery services and 2.8% were dissatisfied with midwifery services. Discussion: With looking at these results it can be concluded that maternal satisfaction can be influenced by the midwifery services provided. Therefore health professionals must pay attention to comfort, friendliness and continuous and continuous costs to the community, especially women giving birth to the services provided, so that mothers can feel more satisfied with the services provided both from the place of delivery, health care workers and eligibility costs provided are in accordance with the services provided. But if there is a shortage of services, it is expected that the mother can provide advice to health workers.